Smart ball : marketing the myth and managing the reality of major league baseball - Lewis, Robert (Robert F.) (University Press of Mississippi, 2010)
Lewis follows Major League Baseball (MLB)'s history as a sport, a domestic monopoly, a neo-colonial power, and an international business. MLB's challenge has been to market its popular mythology as the national pastime with pastoral, populist roots while addressing the management challenges of competing with other sports and diversions in a burgeoning global economy. The author argues that MLB for years abused its legal insulation and monopoly status through arrogant treatment of its fans and players and static management of its business.